2017
DOI: 10.1063/1.4996678
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network intelligent method for prediction

Abstract: Coupling and power transfer efficiency enhancement of modular and array of planar coils using in-plane ringshaped inner ferrites for inductive heating applications Journal of Applied Physics 122, 014902 (2017) Abstract. Accounting and financial classification and prediction problems are high challenge and researchers use different methods to solve them. Methods and instruments for short time prediction of financial operations using artificial neural network are considered. The methods, used for prediction of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…ANNs were established to imitate the architecture of the biological brain of humankind [ 27 ]. They are able to discover the nonlinear relationship in the input data set [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…ANNs were established to imitate the architecture of the biological brain of humankind [ 27 ]. They are able to discover the nonlinear relationship in the input data set [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…al. [23] suggested that the optimum number of neurons in the hidden layer could be estimated by N/2, where N is the number of input variables or experimental data. The tangent sigmoid transfer function (tansig) and linear transfer function (purelin) were applied to the hidden layer and output layer, respectively.…”
Section: Neural Network Modelingmentioning
confidence: 99%
“…Trifonov conducted a study on the architecture of a neural network which used four different technical indicators [6]. For UTOMO, improving optimization in stock price predictions can be done using a gradientbased back propagation neural network approach.…”
Section: Literature Reviewmentioning
confidence: 99%